Armenia : Technical Assistance Report-Upgrading Fiscal Rules. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the technical advice and recommendations given by the IMF mission to the authorities of Armenia regarding design of fiscal rules and associated fiscal and institutional frameworks. Armenia has made significant strides in enhancing macroeconomic stability over the past two decades. Although Armenia's public debt remains sustainable, a prolonged adjustment is needed to restore sizable fiscal buffers, warranting an upgrade of the fiscal rule framework. The existing debt-rule-based framework provides insufficient operating guidance to fiscal policy and is not flexible enough to deal with severe economic shocks. Mechanisms to deal with a potential breach of the 60 percent debt ceiling and the 50 percent debt brake are excessively restrictive and need to be overhauled.